Teachers’ and students’ perceptions of factors causing high school students’ speaking anxiety : - Đào, Nguyễn Anh Đào (Trường Đại học Cần Thơ, 2018)
The study attempts to determine the perceptions of the students and the teachers of factors causing speaking anxiety in the EFL classes. The key aims of this research are to find out the differences between the students’ and teachers’ perceptions of the factors causing high school students’ speaking anxiety.